Enhancing Operational Risk Management in The Commercial Explosives Sector: A Case Study of PT Tasun Anugerah Bersama - Aini, Sepdia Qurrota; Megawati, Lokita Rizky; Indrawan, Dikky (Business Review and Case Studies, 2024)
Background: The demand for commercial explosives is rising in tandem with the growth of infrastructure development in Indonesia. Companies like PT Tasun Anugerah Bersama, which provides licensing and distribution services for commercial explosives, face multiple operational risks that require effective risk management. Despite this, PT Tasun has not yet implemented a comprehensive risk management system. Purpose: This study aims to assess the scope of operational risks, analyze risk levels, and recommend appropriate risk management strategies for PT Tasun. Design/Methodology/Approach: The research utilizes a risk management framework integrating Godfrey risk control and the risk treatment methods by Flanagan and Norman. It incorporates ISO 31000:2018 for risk management and ISO 45001:2018 for Occupational Health and Safety (OHS). Findings/Result: The research identifies 26 operational risks, including 14 low-level, 9 moderate-level, 2 high-level, and 1 extreme-level risk. The focus is on managing high and extreme-level risks to enhance business sustainability. Conclusion: Implementing structured risk management in accordance with ISO standards can significantly minimize operational risks and improve company performance. Originality/Value: This study provides a novel approach by integrating ISO 31000:2018 and ISO 45001:2018 standards to address the specific operational risks in the commercial explosives sector, offering valuable insights for companies facing similar challenges in high-risk industries. Keywords: commercial explosives, operational risk, risk management, SNI ISO 31000:2018, SNI ISO 45001:2018